3, 3 diindolylmethane leads to apoptosis, decreases sperm quality, affects blood estradiol 17 β and testosterone, oestrogen (α and β) and androgen receptor levels in the reproductive system in male rats. (29th February 2016) - Aksu, E. H.; Akman, O.; Ömür, A. D.; Karakuş, E.; Can, İ.; Kandemir, F. M.; Dorman, E.; Uçar, Ö.
Summary: 3, 3 Diindolylmethane (DIM) is a major digestive product of indole‐3 carbinol, obtained from Brassica family vegetables such as broccoli, cabbage and Brussels sprouts. This study aimed to investigate the effects of DIM on sperm parameters, histological structures of testicular tissues, blood testosterone (T) and estradiol 17‐β (E2) in male rats. Thirty‐eight male Sprague Dawley rats were used. Rats were divided into four groups: Group I: referred as Control group, received corn oil only; Group II: as DIM‐10, rats received 10 mg kg −1 DIM; Group III: as DIM‐50, rats received 50 mg kg −1 DIM; Group IV: as DIM‐100, received 100 mg kg −1 DIM during 53 days. Spermatological parameters, malondialdehyde (MDA) levels of testes and serum T and E2 levels were assayed. Histopathological examinations of tests were done. DIM caused an increase in MDA levels. It decreased motility and live sperm rates and increased degeneration of testicular tissues. While DIM‐10 did not affect abnormal sperm rate, higher concentrations increased the abnormalities. Sperm density was higher in DIM‐10 groups when compared to both other groups. Only DIM‐50 had an anti‐androgenic effect among all groups. Only, DIM‐10 showed anti‐estrogenic activity as compared to higher DIM groups. In conclusion, DIM (i) had side effect on some sperm characteristics, (ii) increased the MDA levels and (iii) led to histological degeneration of testicular tissues and apoptosis in a dose‐dependent manner.